Shelley Jacksons’s Gender Politics in Patchwork Girl (1995): a Cyborg Approach - Anne-Laure Fortin-Tournès (Centre de Recherche "Texte et Critique de Texte", 2021)
As a complex fragmented and “syncopated” hypertext, Patchwork Girl by Shelley Jackson interpellates its reader to place hze in the position of multiple, interconnected subject whose task is to piece together the creature in and of the text, through the physical action of clicking on the hyperlinks. Piecing the female body and the body of the text together in order to read “herstory” forces the reader to adopt a position that ceases to be one of mastery and domination traditionally associated with the reading of print fiction. Rather, Patchwork Girl prompts the reader into adopting a gaze that is “modular and fragmentary” and facilitates her active participation in the textual criticity inherent in the rhizomatic form of the hypertext. By appealing to the reader’s demiurgic powers of imagination, the hypertext replaces the identity paradigm with the performance paradigm. The patched body of the monstrous female serves as a powerful metaphor for the hypertext itself and its capacity as a “feminine form” (Jackson) to deconstruct the binaries and boundaries introduced by modern science at the service of male hybris, which Mary Shelley’s Frankenstein, one of the key intertexts of Patchwork Girl, forcefully denounced. Thanks to its paradoxical materiality, the hypertext equates the female creature’s body with the monstrous form generating it. Thus, the technological medium makes it possible for Jackson to graft the text as body onto the body as text to deconstruct the logic of male-dominated technocapitalism. Engaging with the hypertext implies for the reader the letting go of the binaries (text/body, text/sex, text/technology) structuring traditional reading. Thus Patchwork Girl sollicits a “cyborg” approach (Hayles) which welcomes and performs multiple, hybrid forms of interconnectedness allowing for the creation of new subjective modalities in and of the text.